Model of Quality Assurance Implementation Based on Mentoringin SMP City of Semarang - Slamet Slamet; Heri Yanto; Sri Wardhani; Arief Yulianto; Joko Sutarto (Universitas Negeri Semarang, 2021)
The purpose of this study is to develop a mentoring-based accreditation implementation model, by: (1) describing and analyzing a factual model for junior high school accreditation which includes: (a) school preparation in conducting accreditation; (b) the mechanism for implementing school accreditation; and (c) follow up on the results of school accreditation; (2) produce a hypothetical model design for the implementation of accreditation in junior high schools that can develop the inherent internal commitment of school managers, describe the results of school performance as a whole, as well as can be used as a reference in school development; and (3) produce a final model for implementing school accreditation in junior high schools that can develop the inherent internal commitment of school managers, describe the results of school performance as a whole, as well as can be used as a reference in school development. This research was carried out using the method of developing a procedural model by modifying the research and development design (Educational Research & Development). The results obtained are the final model for implementing school accreditation in junior high schools, which can develop the inherent internal commitment of school managers, describe the results of school performance as a whole, as well as can be used as a reference in school development. The conclusions in this study are: 1) the implementation of quality assurance in schools has not been maximized 2) the quality assurance system has not been owned by each school, if there is accreditation, it is only prepared a few weeks before the assessor visits 3) the quality assurance process has been carried out well, although not optimal. 4) internal quality assurance has not been able to reflect the quality of school quality. and 4) still weak supervision by supervisors and principals. Solutions to overcome deficiencies in planning, implementation, and evaluation of quality assurance implementation need regular assistance from various parties, ranging from school principals, teachers, school supervisors and the education office as well as other relevant agencies.